Précis of correspondence relating to Zanzibar affairs from 1856 to 1872. Prepared by Captain P D Henderson, attached to the Foreign Department - Henderson, P. D. (British Library, 1872)
The file is a précis of correspondence related to affairs at Zanzibar between the years 1856 and 1872, prepared by Captain Philip Durham Henderson of the Foreign Department in the Government of India. The contents of the précis, which includes reports from Christopher Palmer Rigby, the British Consul at Zanzibar, and Sir William Marcus Coghlan, relate to: the death in 1856 of the Sultan of Muscat Syed Saeed [Sa‘id bin Sulṭān al-Sa‘id] without a direct heir; the succession struggle between Syed Thoweynee [Thuwaynī bin Sa‘id al-Sa‘id] and Syed Majid [Sa‘id Majid bin Said al-Sa‘id]; British arbitration in the dispute; succession arrangements at Muscat and Zanzibar; the slave trade between Zanzibar and Muscat. The précis is organised into six chapters (labelled I to VI), as follows: I – Events preceding the arbitration by the Government of India; II – Arbitration of the Government of India; III – Proceedings subsequent to the arbitration relating to the question of subsidy; IV – Events at Zanzibar from the arbitration to the death of Syed Majid; V – Events in Zanzibar from the death of Syed Majid; VI – Slave Trade. The contents page lists four appendices (labelled A to D) that are not included in this copy of the précis.
Keywords: Zanzibar

Mr Rothery's report to the Treasury in respect to the Muscat subsidy and Zanzibar Agency Expenses - Moore, Adolphus Warburton (British Library, 1876)
A printed memorandum, written by Adolphus Warburton Moore, Assistant Secretary of the Political and Secret Department of the India Office, 27 September 1876. The memorandum discusses the views of Henry Cadogan Rothery on whether the Imperial Government had to contribute to the payment of an annual subsidy to the Sultan of Muscat (as compensation for the abandonment of his claims upon Zanzibar) and of the expenses of the Agency and Consulate at Zanzibar, made by the India Office from 1870. Rothery writes that, because the Agent at Zanzibar was also acting as Judge of the Vice Admiralty Court in the Trial of the Slave Trade cases, it was the duty of the Imperial Government to contribute towards these expences.
Keywords: Zanzibar

Report of a committee on the Muscat subsidy and the Zanzibar Agency and Consulate - Mallet, Louis; Rothery, Henry Cadogan; Wylde, William Henry (British Library, 1876)
A printed report, written by a Committee formed by Louis Mallet, Henry Cadogan Rothery and William Henry Wylde, 8 December 1876. The Committee was nominated by H M's Treasury, the Secretary of State for Foreign Affairs and the Secretary of State for India, to determine whether the Imperial Government had to contribute to the payment of an annual subsidy to the Sultan of Muscat (as compensation for the abandonment of his claims upon Zanzibar) and of the expenses of the Agency and Consulate at Zanzibar, which had been paid by the India Office since 1870. The committee acknowledges that in 1873 it was agreed that these payments should be divided between Imperial and Indian Government, hence the Imperial Government had to compensate the India Office for the payments made in the years 1873-1877. The report includes a summary of payments made to the Sultan of Muscat between May 1873 and February 1877, expenses for the British Agency and Consulate General at Zanzibar for the period 1872-1877, and a proposed budget estimate for the future, to be equally divided between Imperial and Indian Government. Two declarations follow the report, from two comissioners in disagreement with the report.
Keywords: Zanzibar

Memorandum No 1. Zanzibar Agency and Consulate Expenses - Moore, Adolphus Warburton (British Library, 1876)
A printed memorandum, written by Adolphus Warburton Moore, Assistant Secretary of the Political and Secret Department of the India Office, 17 August 1876. The first part of the document is a claim of expenses for an annual subsidy of 40,000 crowns from the Sultan of Zanzibar to the Sultan of Muscat as compensation for the abandonment of his claims upon Zanzibar, which was paid by the Political Agent at Muscat for the period 1870-1877, including a summary of payments made between May 1873 and February 1877. The second part of the document contains a claim for the expenses of the Agency and Consulate at Zanzibar, including: salary of Political Agent, Second Assistant and interpreters, furlough allowances and charge for interest on Government buildings.
Keywords: Zanzibar

The Exploration of Socotra - Sclater, P.L. (Nature, 1879)
Keywords: Zanzibar

Socotra - Sclater, P.L. (Nature, 1876)
Keywords: Zanzibar

Notes on Socotra - Hunter, F. M. (The Journal of the Anthropological Institute of Great Britain and Ireland, 1878)
Keywords: Zanzibar